Total chemical synthesis of human T-cell leukemia virus type 1 protease via native chemical ligation - Li, Changqing; Li, Xiangqun; Lu, Wuyuan (Biopolymers, 2010)
Human T‐cell leukemia virus 1 (HTLV‐1) protease, a member of the aspartic acid protease family, plays critical roles in the pathogenesis of the virus and is an attractive viral target for therapeutic intervention. HTLV‐1 protease consists of 125 amino acid residues and functions as a homodimer stabilized in part by a four‐stranded β‐sheet comprising the N‐ and C‐termini. Compared with many other viral proteases such as HIV‐1 protease, HTLV‐1 protease is elongated by an extra 10 amino acid residue “tail” at the C‐terminus. The structural and functional role of the extra C‐terminal residues in the catalysis of HTLV‐1 protease has been a subject of debate for years. Using the native chemical ligation technique pioneered by Kent and coworkers, we chemically synthesized a full‐length HTLV protease and a C‐terminally truncated form encompassing residues 1‐116. Enzyme kinetic analysis using three different peptide substrates indicated that truncation of the C‐terminal tail lowered the turnover number of the viral enzyme by a factor of 2 and its catalytic efficiency by roughly 10‐fold. Our findings differ from the two extreme views that the C‐terminal tail of HTLV‐1 protease is either fully dispensable or totally required for enzyme dimerization and/or catalysis. © 2010 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 94: 487–494, 2010.